2011
DOI: 10.1007/s11255-011-9966-1
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of renal abnormalities in patients with psoriasis

Abstract: The presence of abnormal urinalysis was not more common in patients with psoriasis than in controls. However, the increased prevalence of pathologic albuminuria and its positive correlation with psoriasis severity may suggest subclinical glomerular dysfunction in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 22 publications
2
39
0
4
Order By: Relevance
“…Although psoriasis is a common chronic inflammatory disorder of the skin, increasing evidence has demonstrated that psoriasis is associated with an increased risk of CKD and urinary albumin excretion [26, 27]. A population-based cohort study demonstrated that moderate to severe psoriasis was associated with an increased risk of CKD, independent of traditional risk factors [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although psoriasis is a common chronic inflammatory disorder of the skin, increasing evidence has demonstrated that psoriasis is associated with an increased risk of CKD and urinary albumin excretion [26, 27]. A population-based cohort study demonstrated that moderate to severe psoriasis was associated with an increased risk of CKD, independent of traditional risk factors [10].…”
Section: Discussionmentioning
confidence: 99%
“…In another cross sectional study, Yang et al reported that renal failure was more prevalent in patients with severe psoriasis than in age- and sex-matched controls [28]. In addition, multiple cross-sectional studies had also observed a greater prevalence of microalbuminuria [26]. Psoriatic nephropathy is recently described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Bu nedenle, psöriyazisli hastalarda hem arteryel hem de venöz tromboembolik olaylar açısından dikkatli olunmalıdır. 12 Sol böğür ağrısı şikâyeti ile başvuran erişkin psöriyazisli bu olgumuzda, hematüri ve yüksek serum LDH düzeyi saptanmasıyla renal infarktüsten şüphelenilmiş, arteryel tromboza neden olabilecek çevresel ve genetik etkenler, aile anamnezi ve eşlik eden venöz tromboemboli varlığı araştırılmış, sigara kullanma ve psöriyazis hastalığı dışında ek bir predispozan faktör tespit edilememiştir.…”
Section: Discussionunclassified
“…131,132 In a population-based cohort study, psoriasis was an independent risk factor for moderate to advanced chronic kidney disease among patients with severe psoriasis, but not for individuals with mild psoriasis. 131 Furthermore, the age specific adjusted hazard ratio for individuals with chronic kidney disease was 3.82 (95% CI, 3.15-4.64) for patients aged 30 and 2.00 (95%CI, 1.86-2.17) for patients aged 60, demonstrating the greater risk among the younger age group compared with individuals without psoriasis in similar age groups, suggesting that individuals with psoriasis may be affected with chronic kidney disease at a younger age than those without psoriasis.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%